The resurgence of rheumatic fever in a developed country area: the role of echocardiography. - Pastore, Serena; De Cunto, Angela; Benettoni, Alessandra; Berton, Emanuela; Taddio, Andrea; Lepore, Loredana (Rheumatology (Oxford), 2011)
OBJECTIVES: The annual incidence of ARF ranges from 5 to 51/100, 000 population worldwide in the 5- to 15-year age group. In the past, there was a decline in the incidence of ARF; however, focal outbreaks have been reported. This study evaluated the incidence of ARF in 2007-08 in a region of a developed country compared with the previous decade. METHODS: A retrospective review of all admission records for ARF in Trieste between January 2007 and December 2008 was undertaken. The diagnosis of ARF was established by the Jones criteria according to the 1992 revision. RESULTS: Between January 2007 and December 2008: 13 cases of ARF were recorded, 11 females and 2 males. The estimated incidence was 23 and 27/100, 000 population new cases each year, respectively, in the 5- to 15-year age group. Migratory polyarthritis occurred in 6/13, chorea in 7/13 and clinical carditis in 5/13 cases. Five out of 13 patients had only echocardiographic abnormalities, with no clinical cardiac manifestations. Another two patients did not fulfil diagnostic criteria for ARF, presenting with only three minor criteria, but they revealed silent carditis at echocardiography evaluation. During the follow-up, in one case the carditis receded and in the other it significantly improved. CONCLUSIONS: Our experience underlines that ARF has not yet disappeared in industrialized countries. We observed a high incidence of chorea, always associated with mild carditis. Echocardiographic assessment should be routinely performed in all patients with suspected ARF in order to identify those subclinical cases of valvulitis that would otherwise pass undiagnosed without receiving proper prophylaxis.
Keywords: Adolescent; Child; Child, Preschool; Chorea; Developed Countries; Diagnosis, Differential; Echocardiography; Female; Humans; Italy; Male; Myocarditis; Retrospective Studies; Rheumatic Fever